Pengaruh Capital Adequacy Ratio, Bank Size, Profitability, Liquidity, terhadap Non Performing Loan dengan Kepemilikan Institusional sebagai Pemoderasi pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia (2018 - 2023) - Ichsan, Hamzah; Marsono, AD (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2025)
The turning of the economic wheels in a country can never be separated from the financial sector, especially banking which has become an intermediary in financing from upstream to downstream. Banking has a very important role in the growth and stability of the economy. It can be seen that when there is a decline in the economic sector, the banking sector is one of the things that is reorganized by the government to restore economic stability. Banking as a financial intermediation institution has the main function of channeling credit from parties who have excess funds to parties who need funds.Appropriate credit distribution will be able to provide profits for the bank based on the difference in interest on the loan taken. The large amount of credit given will result in a large risk borne by the bank concerned due to the large number of problem loans that occur in a bank. The level of problem loans is usually reflected by the bank's non-performing loan (NPL) ratio, which is used to measure the bank's ability to overcome the risk of failure to repay credit by debtors.NPL reflects the bank's ability to manage credit and implement risk management in the credit distribution process. NPL is the percentage of bad debt, calculated by comparing the number of bad loans with the total amount of credit. Banks have to take a high risk of bad credit due to the high number of bad loans. NPL is credit in which there are obstacles caused by 2 (two) elements, namely from the banking side in analyzing it and from the customer who intentionally or unintentionally does not make payments in their obligations. Problematic credit is caused by irregular payments of loan principal and interest which can directly reduce bank performance and cause the bank to be inefficient.According to the Financial Services Authority (OJK), the ratio of non-performing loans or banking NPLs was recorded to have increased in July 2023 in terms of gross and net NPLs in the July 2023 period, respectively, amounting to 2.51% and 0.80%. This figure is higher than the previous month's levels of 2.44% and 0.77% respectively.